PERHITUNGAN BEBAN KRITIS STRUKTUR PLASTIS DENGAN MENGGUNAKAN METODE SOUTHWELL - Sebayang, Darwin (BRIN Publishing, 2003)
The structure of the cylinder can be found in the structure of a rocket, an aircraft of chimney. The stability of the cylinder is very important to know the capability cylinder to support the load. It is required to give a load up to plastic region in order to optimize the load capability of the material. Therefore it is required to obtain the procedure to calculate the plastic buckling. Herewith it is shown the Southwell's Method to calculate the plastic buckling of the cylinder made of the non linear material. The approximation based on the Ramberg-Osgood is used to illustrate the stress-strain diagram. The diagram of Karman is used to obtain the Modulus of elasticity which is valid for the plastic region. The result based on this method are campared to the experimental data. The results are satisfactory. This method can be used to calculate the critical load of the LAPAN's rocket by considering the plasticity of the material and structure can be lighter.